Asymmetry in hip, knee and ankle kinematics in cyclists with chronic unilateral patellofemoral pain - Brand, Erika Gertruida (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScPhysio)--Stellenbosch University, 2016.